Oral health profile of the elderly people in the Pandalungan community - Amandia Dewi Permana Shita; Zahreni Hamzah; Zahara Meilawaty; Tecky Indriana; Ari Tri Wanodyo Handayani; Dyah Indartin Setyowati (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: The Pandalungan community is a unique community established through the assimilation of two dominant cultures: the Javanese and Madurese. Both of these communities created a community with a new culture called the Pandalungan community culture. The people of this community live in coastal, rural and urban areas. Generally, research on the uniqueness in the oral health behaviour of the Pandalungan community has not been conducted since the oral health practices of the Pandalungan community are considered to be the same as that of the Javanese community. Purpose: In order to develop programmes for oral health prevention, this research aims at comparing the oral health profiles of the elderly (classified as per age) living in the rural and urban areas in the Jember Regency. Methods: The research employs a cross-sectional approach. The subjects of the research were selected on the basis of the total number of elderly people who attended the monthly meetings of the Karang Werda (those not willing to participate in the study were excluded). The study was conducted by organising extensive interviews, performing observations and intraoral examinations. Each group was classified into three subgroups on the basis of age: pre-elderly, elderly and high-risk elderly. The intraoral examination conducted included the oral hygiene index-simplified (OHI-S), the number of teeth missing, the depth of the pocket and the number of all functional tooth units (all-FTU). Results: The oral health profile of people in the rural community was poor when compared to the oral health profile of people living in the urban community (by accounting for nearly all the variables in the examination). Conclusion: The oral health profile of the elderly people in the Pandalungan community was poor. Adequate prevention and care are essential to maintain the oral health of people in the Pandalungan community.